2015
DOI: 10.1186/s40712-015-0047-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of friction-stir-welded polyamide sheets

Abstract: Background: In this study, the effect of processing parameters on the mechanical properties of friction-stir-welded polyamide (nylon 66) sheets is investigated. Methods: Commercial polyamide sheets with the dimension of 250 × 150 × 8 mm are used in experimentations. The processing parameters considered in the welding include: rotational speeds in five levels and traverse speeds in three levels. Tensile and impact tests are performed in order to evaluate mechanical behavior of welded sheets. Full-factorial desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The ANOVA results of all the studies are summarized in Table 8. Several thermoplastic materials have been investigated for butt-joint FSW, which include HDPE [1], Nylon-66 [99], glass-filled Nylon 6 (30 wt.%) [104], HMWPE (Teflon stationary shoulder tool with threaded pin) [168], polyamide-6,6 (tapered cylindrical pin) [113], and ABS (3D-printed, wooden stationary shoulder) [43]. All these studies have suggested that rotational speed is the first and traverse speed is the second most influential parameters that affect joint strength.…”
Section: Statistical-based Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The ANOVA results of all the studies are summarized in Table 8. Several thermoplastic materials have been investigated for butt-joint FSW, which include HDPE [1], Nylon-66 [99], glass-filled Nylon 6 (30 wt.%) [104], HMWPE (Teflon stationary shoulder tool with threaded pin) [168], polyamide-6,6 (tapered cylindrical pin) [113], and ABS (3D-printed, wooden stationary shoulder) [43]. All these studies have suggested that rotational speed is the first and traverse speed is the second most influential parameters that affect joint strength.…”
Section: Statistical-based Studiesmentioning
confidence: 99%
“…The total contribution of these two parameters on joint strength have been reported from 61.50% to 94.03%, with the contribution of rotational speed from 40.10% to 79.60% and traverse speed from 10.77% to 35.03%. Also, it has been reported that rotational speed is the most significant parameter, followed by traverse speed for impact strength [99] and percent elongation [104]. Adibeig et al [122] have studied PMMA using a double-step shoulder tool with threaded pin.…”
Section: Statistical-based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, FSW is only applicable to thermoplastics [ 28 ]. This technique has successfully joined: acrylonitrile butadiene styrene (ABS) [ 29 , 30 , 31 , 32 ], polyamide 6 and 66 (PA6 and PA66) [ 33 , 34 , 35 ], polycarbonate (PC) [ 36 , 37 ], polyethylene (PE) [ 25 , 38 , 39 ], polylactic acid (PLA) [ 40 ], polymethylmethacrylate (PMMA) [ 41 , 42 , 43 ], polypropylene (PP) [ 44 , 45 , 46 ] and polyvinyl chloride (PVC) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moshwan et al [25] produced hybrid polycarbonate/AA7075 joints by FSW while Liu et al [26] joined polyamide (PA) to AA6061 by friction lap welding. Husain et al [27] optimized the processing conditions for joining PA sheets. Azarsa et al [28] then used a heated stationary shoe-shaped shoulder to produce metal polymer composites during FSW.…”
Section: Introductionmentioning
confidence: 99%